2010
DOI: 10.1007/s10823-010-9134-6
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Filial Obligation and Their Impact on Preferences for Future Living Arrangements of Middle-Aged and Older Asian Indian Immigrants

Abstract: Filial obligation, described as culturally-defined rights and duties that prescribe how family members are expected to care for and provide support to each other, is an important variable that influences older immigrants' preferences for living and care arrangements. This exploratory study examined variables associated with expectations of filial obligation among middle-aged and older, Asian Indian, first generation immigrants and explored the relationship between variations in expectations of filial obligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
1
26
2
Order By: Relevance
“…This finding was consistent with those of previous studies. A study among middle-aged and older Asian Indian immigrants reported that the most popular preference for future living arrangements was to “move closer to children” [15]. Bian et al [30] found a similar co-residence pattern “proximity to parents” in urban China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was consistent with those of previous studies. A study among middle-aged and older Asian Indian immigrants reported that the most popular preference for future living arrangements was to “move closer to children” [15]. Bian et al [30] found a similar co-residence pattern “proximity to parents” in urban China.…”
Section: Discussionmentioning
confidence: 99%
“…The number of surviving children (classified into 3 categories: zero, one and two or more) has been extensively used in similar studies [16, 19]. The availability of children, based on a previous study [15], was classified into 3 categories: daughters only, sons only, and daughters and sons. Self-rated health was categorized as poor, fair, good, and very good/excellent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, researchers have started to explore elderly preferences for future living arrangements and care and the factors correlated with these preferences (e.g., Diwan et al 2011;Harrefors et al 2009;Pinquart and Sorensen 2002;Roberto et al 2001). The findings varied from one society to another.…”
Section: Care Preferencesmentioning
confidence: 99%
“…For example, in a sample of Hispanic immigrants in the U.S., Kao and Travis [13] found that being older, female, and less acculturated was related to increased expectations of filial obligation. In contrast, a study of Asian Indian immigrants found no correlations between filial obligation expectations and education or length of residence in the US [14]. …”
Section: Introductionmentioning
confidence: 99%